Effective separation of protein from Polygonatum cyrtonema crude polysaccharide utilizing ionic liquid tetrabutylammonium bromide - Xu, Yuling; Xu, Jing; Fan, Zheng; Zhang, Siyuan; Wu, Yuanjie; Han, Rongchun; Yu, Nianjun; Tong, Xiaohui (Frontiers in Chemistry, 2024)
Extraction of plant polysaccharide often results in large amount of protein which is hard to eliminate from the crude extract and conventional approaches for deproteinization are time-consuming and often involve hazardous organic solvents. In this study, the ionic liquid tetrabutylammonium bromide (TBABr) was used to create an ionic liquid aqueous two-phase system (ILATPS) for the separation of polysaccharide (PcP) and protein extracted from rhizome of Polygonatum cyrtonema.Bovine serum albumin (BSA) was first applied to assess the feasibility of the ILATPS and MgSO4 was determined to be the most suitable inorganic salt. By adopting the Taguchi experiment with a L9 (3^4) orthogonal array, it was found that the best condition for efficient separation of crude PcP was 25 ℃ , 1.5g of TBABr, 15mg of PcP and 2.0g of MgSO4, with the extraction efficiency for protein and polysaccharide as 98.6% and 93.5%, respectively. The purified PcP was homogeneous and its weight average molecular weight (Mw) was 7554 Da. Monosaccharide composition analysis indicated the PcP was comprised of mannose, galactose, glucose, galacturonic acid, arabinose and rhamnose with a molar ratio of 33:13:8:3.5:2:1. This approach offers a practical tactic to purify polysaccharide of plant origin.